Avaliação microbiológica do queijo Minas artesanal comercializado no mercado central da cidade de Montes Clares, norte de Minas Gerais - Grace Kelly Alves de Melo (2021)
Cheese is one of the most produced and consumed dairy products in Brazil and there is a concern to maintain the quality of the cheese produced, both in its handling and processing, as it is vulnerable to contamination that can harm the consumer's health. This work aimed to investigate the microbiological characteristics of 32 handmade Minas cheeses sold in the Central Market in the municipality of Montes Claros, northern Minas Gerais. As a result of microbiological analyzes of Coliforms at 30°, Escherichia Coli and Staphylococcus aureus, they ranged from 4.10 (Log cfu/ml) to 7.21 (Log cfu/ml), 5.14 (Log cfu/ml) to 6, 98 (Log cfu/ml) and 6.05 (Log cfu/ml) to 7.39 (Log cfu/ml), respectively. All 32 cheeses had negative results for Listeria monocytogenes and Salmonella sp.. Microbiologically, the samples were unfit for consumption, as they presented a count of microorganisms above the limits specified by legislation. It is concluded that there is a need to implement improvements in production control that highlight the importance of good cheese manufacturing practices.